POTENSI PEMANFAATAN ATAP GEDUNG PUSAT PEMERINTAHAN KABUPATEN BADUNG UNTUK PLTS ROOFTOP - I Dewa Gde Yaya Putra Pratama; I Nyoman Satya Kumara; I Nyoman Setiawan (Jurnal SPEKTRUM, 2018)
In the RUPTL PT PLN Years 2017 untill 2026, the goverment aim to reach 5000 MW of PV plant potential in 2025. But, until November 2016, the number of PV plant in Indonesia is around 11 MW. To reach the 5000 MW target, many approach must be use. One of the approach is install PV plant on goverment buildings. Pusat Pemerintahan Kabupaten Badung (Puspem Badung) is a goverment buildings complex which located in Badung Regency, Bali is one of the goverment building that can be use for this approach. This paper aim to know the potency of electrical power dan electrical energy produced by Puspem Badung if the PV plant installed on the north, east, west, and south side of the roof. Electrical energy produced by PV plant is simulated by using System Advisor Model (SAM). From the simulation results, north side of the roof can produce energy of 1.847.361 kWh/year. From the analysis, the total energy that can be produced by PV plant is 6.169.092 kWh/year. This amount can supply Puspem Badung energy need by 124,72 %.